Accounting Treatment of Dividend Policy in Moderating Company Performance on Company Valuation - Nainggolan, Yohanna Thresia; Putri, Ferica Christinawati; Rahmawati, Meylin; Rahmawati, Kartini; Irna, Rizky Agusriyanti; Irna, Mardiyah (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2024)
This study aims to determine the accounting treatment of dividend policy in moderating the company's performance against the company's valuation in companies included in the LQ45 index for the 2018-2022 period. This study uses secondary data whose source comes from the annual financial statements on the Indonesia Stock Exchange, especially companies included in the LQ45 index. The analysis techniques used in this study are multiple regression analysis and Moderated Regression Analysis (MRA). This study shows the results that profitability proxied by return on equity has no effect on the company's valuation, the solvency ratio proxied by the debt to equity ratio has a significant influence on the company's valuation in a negative direction and the dividend policy proxied by the dividend payout ratio Able to moderate the ratio of profitability to company valuation and dividend policy is unable to moderate the ratio of solvency to company valuation which is proxied by the dividend discount model